Synchronized swimming: The influence on young and adolescent girls` development and eating habits - Romero, A. (ValUE, 2020)
Establishing the ideal weight and body composition for each sport is important for athletic performance, but concurrently, dissatisfaction with body image and an obsession with thinness may result in poorer performance and health issues (Hagmar et al., 2008).